La funzione mitopoietica della lingua euripidea. Alcune osservazioni sulla traduzione di Friedrich Hölderlin «Die Bacchantinnen» (Studia theodisca, 2019)
Based on a philological analysis of the translation of Euripides’ Bacchae by Hölderlin, this paper examines the syntactical and semantic choices made by the translator and aims to investigate the adaptation of the ancient lexicon to his contemporary expressive needs. Every voluntary violation of the syntactic order of the phrases, as well as every semantic choice that diverges from the original Greek text, which is usually translated word by word, represents a conscious modification of the “sacred” Greek archetype, and allows the poet to turn the translation into his own “place of poetic creation”.